Validation of Self-reported Oral Health Measures - Waranuch Pitiphat, DDS, MPHM, MS; Raul 1. Garcia, DMD, MMedSc; Chester W. Douglass, DMD, PhD; (Blackwell Synergy, 2002)
To assess the validity of self-reported oral disease and health care measures in two populations